Management of disease related anaemia in cancer patients - Rolski, Janusz; Pawlicki, Marek; Zemełka, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2002)
Cancer related anaemia (CRA) is reported in 50% of cancer patients. Characteristically CRA is similar to the anaemia of chronic diseases. Anaemia not only deteriorates the quality of life but has an adverse influence of the treatment outcome. Therefore, the treatment of anaemia is very important in supportive therapy. Blood transfusion is fast and efficient in the treatment of anaemia but it may cause various transfusion-related complications. Erytropoietin (EPO) provides an attractive and safe alternative in the therapy of cancer related anaemia. The guideline panel found good evidence to recommend the use of EPO as a treatment option for patients with a hemoglobin level bellow 10 g/dl. Good evidence from clinical trials supports the use of subcutaneous EPO 150 u/kg thrice a week for a minimum of 4 weeks. Dose escalation should be considered for those not responding to the initial dose. In the absence of response, continuing EPO beyond 6 to 8 weeks does no't appear to be beneficial. EPO should be titrated once the hemoglobin concentration reaches the level of 12 g/dl. The main indication for EPO therapy in oncology is anaemia following administration of platinum - containing regimens. Anaemia in multiple myeloma and low-grade lymphoid malignancies responds to EPO therapy in as many as 50-75% of patients. This is why, based on both clinical and economic grounds, EPO should be considered a preferred alternative to transfusion, especially in patients who are likely to experience chemotherapy and radiotherapy induced anaemia and those at higher risk of transfusion-related complications.